Naruszenie „godności zawodu lekarskiego” z perspektywy lekarzy i lekarzy dentystów: studium deontologiczno-prawne - Zieliński, Piotr; Radkowska-Gizelska, Małgorzata; Sliż, Piotr (PRAWO i WIĘŹ, 2026)
The issue of the “dignity of the medical profession” is an important field of research with an interdisciplinary dimension. The aim of this paper is to identify the extent of understanding, interpretative coherence and practical application of the concept of the “dignity of the medical profession” by physicians and dentists, in the context of the applicable Code of Medical Ethics and the jurisprudence of medical courts. In addition, the authors attempted to obtain an answer to the question about the respondents’ self-assessment of their knowledge of the Code of Medical Ethics (KEL). A deliberate decision was made not to try to find out the respondent group’s positions on the understanding of the “dignity of the medical profession,” as the research was devoted to the practical dimension of violations of this dignity, not to the construction of definitions. The research was carried out using a questionnaire survey and the CAWI technique between 2022 and 2024, in Poland, on a non-probabilistically selected group of 201 respondents.